2009
DOI: 10.1093/carcin/bgp034
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive potassium channels control glioma cells proliferation by regulating ERK activity

Abstract: Ion channels are found in a variety of cancer cells and necessary for cell cycle and cell proliferation. The roles of K(+) channels in the process are, however, poorly understood. In the present study, we report that adenosine triphosphate (ATP)-sensitive potassium channel activity plays a critical role in the proliferation of glioma cells. The expression of K(ATP) channels in glioma tissues was greatly increased than that in normal tissues. Treatment of glioma cells with tolbutamide, K(ATP) channels inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 37 publications
8
75
0
1
Order By: Relevance
“…Consistent with similar results obtained in corneal epithelium (20), we have shown that LXA 4 triggered ERK phosphorylation, which mediates LXA 4 -induced proliferation and repair in both non-CF and CF airway epithelial cells. The opposite role of glibenclamide and pinacidil on ERK phosphorylation is consistent with a regulation of ERK activity downstream to K ATP channel activity and recent data showing that that K ATP channels could induce ERK phosphorylation in neuronal and cardiac models (17).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with similar results obtained in corneal epithelium (20), we have shown that LXA 4 triggered ERK phosphorylation, which mediates LXA 4 -induced proliferation and repair in both non-CF and CF airway epithelial cells. The opposite role of glibenclamide and pinacidil on ERK phosphorylation is consistent with a regulation of ERK activity downstream to K ATP channel activity and recent data showing that that K ATP channels could induce ERK phosphorylation in neuronal and cardiac models (17).…”
Section: Discussionsupporting
confidence: 86%
“…In particular, potassium (K ϩ ) channels have been shown in numerous cell types to be involved in cell migration and proliferation (22,26,30,32,44,45). Recent research in glioma tumor cells shows that K ATP channels promote cell proliferation through ERK phosphorylation (17).…”
mentioning
confidence: 99%
“…The upregulation of mitochondrial K ATP channels may activate ERKs. Their activation is associated with cell proliferation and cell survival (Huang et al 2009). Alternatively, salt stress will activate ERKs directly, which leads to the preservation of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Cell transfection was performed as described previously [17]. The sequences of siRNA1 against Kir6.2 are 5-CCAAGAAA GGCAACUGCAATT-3 (sense) and 5-UUGCAGUUGCCU UUCUUG GTT-3 (antisense), siRNA2 are 5-CCAUUGUA GCU GAGGAGGATT-3 (sense) and 5-UCCUCCU CAGC UACAAUGGTT-3 (antisense), and non-silencing RNA are 5-UUCUCCGAACGUGUCACGUTT-3 (sense) and 5-ACGU GACACGU UCGGA GAATT-3 (antisense).…”
Section: Cell Transfectionmentioning
confidence: 99%
“…For example, calcium channels are activated in ischemic neuronal cell death and calcium channel blockers are used in stroke treatment [12]. Considerable evidence exists for the contribution of ion channels to the development and growth of malignant glioma [13][14][15][16][17]. For example, the chloride channel blocking peptide is currently being evaluated in a multi-center phase II clinical trial for glioma [16].…”
Section: Introductionmentioning
confidence: 99%